EXPERIMENTAL STUDIES OF 1500 KW STRAW-FIRED THERMAL GENERATOR OPERATION INDICES - Bodnar, Lilia; Stepanov, Dmytro; Slyvko, Roman (Scientific Works of Vinnytsia National Technical University, 2017)
Application of thermal generators, operating on alternative type of fuel, in particular, straw, is shovn to be one of the most actual problems. Experimental studies of 1500 kW straw-fired generator operation indices are carried out. The rezults of the studies are analyzed. The comparison of calculated and experimental data, regarding the temperature of the gases at furnace outlet is performed. Possibility of the application of Normative Method of boiler units thermal calculation in the process of designing termal generators, operating on alterrnative types of fuel is analyzed.